2018
DOI: 10.1039/c8nr04317e
|View full text |Cite
|
Sign up to set email alerts
|

Molding processed multi-layered and multi-functional nanocomposites with high structural ability, electrical conductivity and durable superhydrophobicity

Abstract: Bioinspired superhydrophobic surfaces mainly attributed to the nano/micro textures and low surface energy materials, have exciting potential usage in fields such as self-cleaning, water-proofing and so forth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…e UV shielding performance of nano-TiO 2 is mainly attributed to the function of TiO 2 to absorb and radiate UV [15]. After research, it was found that nano-TiO 2 is a wide-bandgap semiconductor structure, and the following formula is obtained:…”
Section: Nanometer Tio 2 Uv Shielding Propertiesmentioning
confidence: 99%
“…e UV shielding performance of nano-TiO 2 is mainly attributed to the function of TiO 2 to absorb and radiate UV [15]. After research, it was found that nano-TiO 2 is a wide-bandgap semiconductor structure, and the following formula is obtained:…”
Section: Nanometer Tio 2 Uv Shielding Propertiesmentioning
confidence: 99%
“…For replicating micro/nanostructures onto polymer and rubber surfaces, the imprinting is generally conducted at temperatures below 300 °C. In contrast to that, the formation of micro/nanostructures on metal surfaces requires the imprinting to be conducted at much higher temperatures or pressures in order to realize the replication of fine structural features from templates due to the much lower plasticity of metals compared to that of polymers. Such a high-temperature/high-pressure imprinting process is extremely demanding for the strength of the molding structures on the micro/nanoscales and thus has been rarely realized.…”
Section: Large-scale Cost-effective Fabrication Of Superhydrophobic S...mentioning
confidence: 99%
“…Konduktivitas listrik (238)(239)(240)(241)(242) adalah ukuran kemampuan suatu larutan untuk menghantarkan arus listrik. Arus listrik di dalam larutan dihantarkan oleh ion yang terkandung di dalamnya.…”
Section: Transport Ionunclassified